Association of Periprocedural Haemoglobin Reduction and Myocardial Injury in Patients with Unstable Angina Undergoing Percutaneous Coronary Intervention - Bagchi, Sushil Kumar; Moniruzzaman, Md; Nahar, Sharifun; Khalequzzaman, Md; Chowdhury, Sanjib; Choudhury, Amal Kumar (Journal of Cardiology and Cardiovascular Medicine, 2023)
Background: Patients undergoing percutaneous coronary intervention are at risk of different complications such as periprocedural bleeding and acute hemoglobin reduction that can lead to myocardial injury. Blood loss through the catheter during the procedure and through puncture site haematoma causes periprocedural acute haemoglobin drop. Objectives: To find out the association between acute haemoglobin reduction and myocardial injury after PCI in patients with unstable angina. Methods: This prospective observational study was conducted at the National Institute of Cardiovascular Diseases (NICVD) for one year of time. A total of 130 patients were enrolled based on inclusion and exclusion criteria during the study period. Haemoglobin and troponin-I were measured before and after PCI within 24 to 48 hours of the procedure. On the basis of post-procedural acute haemoglobin level, the study population was categorized into two groups: Group I patients with normal haemoglobin levels and Group II patients with significant acute haemoglobin reduction (≥ 1 gm/dl). Results: A total of 24 patients developed a periprocedural myocardial injury, among them 17 (70.8%) were in the reduced haemoglobin group and 7 (29.2%) in the normal haemoglobin group. Elevation of troponin I after PCI was higher in group II than in group I patients with a statistically significant difference. Multivariate logistic regression analysis showed that haemoglobin reduction was an independent predictor of PMI (OR 1.94; 95% CI, 1.241-8.684; p = 0.01). Conclusion: Periprocedural haemoglobin reduction in patients with unstable angina was associated with myocardial injury after percutaneous coronary intervention (PCI).